(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on the growth and yield of varieties of sunflower grown in irrigated conditions of Uzbekistan - March 10, March 20, March 30, April 10 and April 20, the growing season is 80-85 days, 90-95 and 100-105 days. . Grasses formed from seeds sown in a very early period (March 1 and 10) are susceptible to fungal diseases in the early days of spring under the influence of excess moisture and low temperatures, and the bush numbers are reduced by 1.5–3.2%. Yield is less than 4.3–5.4 ts / ha. As the sowing period is delayed until April 20, during the flowering and ripening phases of sunflower, under the negative influence of high temperatures, the yield is reduced to 0.3-0.7 ts / ha and the oil content in the seeds to 0.3-0.6%. 31-33 ts / ha of early ripening varieties of sunflower grown as the main crop in Samarkand region. and 34.0-35 ts / ha.cha from early middle-aged varieties. It is advisable to sow in the period from March 30 to April 10 to achieve quality yields